IDENTIFIKASI PROFIL KONSUMEN COFFEE SHOP DI BANDAR LAMPUNG (STUDI PADA RUMAH KOPI ROBUSTA COFFEE BUNGA DAN IN AIR CAFE DI LABUHAN RATU) - Josua Aloisius Gonjales Nainggolan; A . Efendi Efendi; Fenny Saptiani (Jurnal Kompetitif Bisnis, 2023)
This research describes the profile of customer jobs, profile customer pains, and profile customer gains in a coffee shop in Bandar Lampung with a focus on taking two places, namely Robusta Coffee Flower Coffee House and In Air Cafe. This type of research is descriptive with a qualitative approach. Data collection was done by documentation, observation, and in-depth interviews with consumers, owners, and employees at Robusta Coffee Bunga Coffee House and In Air Cafe. Sampling was carried out by snowball sampling technique and the validity of the data was proved by triangulation of the source. The results of research and data analysis showed that customer profile jobs in both coffee shop is gathering with friends and doing tasks. In the customer profile pains found complaints from consumers such as a less varied food menu and interior that is less spoiling consumers. While in profile customer gains, consumers expect innovation in food and beverage menus, interior and exterior improvements, and expansion of parking lots. Until the end of the analysis found that the customer profile is more dominant jobs, because consumers come to the coffee shop is more driven for the purpose of gathering with friends. Keywords: profile customer jobs, profile customer pains, profile customer gains.